ANALYSIS OF LIQUIDITY, PROFITABILITY AND WORKING CAPITAL EFFICIENCY AT KPRI â€œMARDISANTOSAâ€ KEBUMEN - Widyasari, Widhi; Rodhiyah, Rodhiyah; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2012)
Koperasi Pegawai Republik Indonesia (KPRI) â€œMardisantosaâ€ is one entity that aims to improve the welfare of its members in Kebumen, its activities include the areas of loan, shops and photocopy services. Management tried to achieve a return in line with expectations, for that management needs to take proper discretion in investing the funds available so that they can achieve the expected liquidity and profitability, and ultimately be able to improve the efficiency of working capital. but in reality KPRI â€œMardisantosaâ€ have not been able to manage their finances efficiently. Based on these conditions, then conducted research on ratio analysis of liquidity, profitability and working capital efficiency at KPRI